Perilaku Prososial Peserta Didik pada Sekolah Menengah Pertama Boarding School Berdasarkan Perbedaan Jenis Kelamin - Alrefi, Alrefi (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2019)
The purpose of this study was to determine the VII grade students’ prosocial behavior of Junior High Boarding School based on genders. The study used a quantitative approach with survey methods. Data measurement tool was a questionnaire in the form of a scale based on indicators of prosocial behavior. The participant were 34 seventh grade students of Junior High Boarding School Academic Year 2017/2018 consisting of 17 boys and 17 girls. The result showed in general prosocial behavior of students in the high category, meaning that students were able to display and show prosocial behavior. Prosocial behavior of male students and female stucents show thatthere were significant differences between female students and male students.